MANUFACTURE OF LIGHTWEIGHT CONCRETE BASED ON ORGANIC WASTE - Ety Jumiati; Masthura Masthura (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2018)
The making of lightweight concrete for lightweight construction materials has been conducted with raw materials based on organic waste from households. The purpose of this study was to utilize household organic waste as aggregate for the manufacture of lightweight concrete. The materials used consist of organic waste, sand, cement, and latex resin with the variation of organic waste composition are 0, 25, 50, 75, and 100% by volume and the addition of latex resin are 10, 12, and 14% by volume. Test parameters performed include density, water absorption, shrinkage, compressive strength, tensile strength, and flexural strength. The result showed that the optimal composition of produced concrete are 25% by volume of waste and 12% by volume of latex resin with the density = 1.46 g/cm3, water absorption = 26.70%, shrinkage = 0.143%, compressive strength = 7.10 MPa, tensile strength = 2.10 MPa, and flexural strength = 2.67 MPa.Keywords: Latex, lightweight concrete, and organic waste.